Social network analysis and the examination of the white right - Lancaster, Thomas David (My University, 2021)
This research paper used Social Network Analysis (SNA) to examine, evaluate the influence of Twitter and other online platforms on Solidarity and Afriforum, two of the most influential white, populist organisations in South Africa. Previous stud ies have conducted enquiries as to the history, structure, and policies of Solidarity and Afriforum. However, to the author’s best knowledge, no academic studies have sought to examine and identity influential opinion leaders within a South African context. The paper aimed to use SNA to create a visual representation of the Twit ter networks of Solidarity and Afriforum to identify the most influential opinion leaders
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, University of the Witwatersrand, 2021
Keywords: Social network analysis; Twitter network; White right; Data